Dependence of minority carrier lifetime of Be‐doped InAs/InAsSb type‐II infrared superlattices on temperature and doping density. Issue 4 (17th November 2015) - Connelly, Blair C.; Steenbergen, Elizabeth H.; Smith, Howard E.; Elhamri, Said; Mitchel, William C.; Mou, Shin; Metcalfe, Grace D.; Brown, Gail J.; Wraback, Michael
Abstract : We investigate the minority carrier lifetime of Be‐doped InAs/InAsSb type‐II superlattices as a function of doping density and temperature using time‐resolved photoluminescence (TRPL) to determine if switching the superlattice type from the typical n‐type residual carrier concentration to p‐type may improve device performance by improving the lifetime–mobility product. The introduction of the Be dopant to the superlattice reduces the carrier lifetime, first by a factor of ∼3 for doping densities near or below the n‐type residual carrier concentration, then by an order of magnitude for samples doped well above the residual carrier concentration. Further, the higher‐doped p‐type samples demonstrate two distinct TRPL decay regimes and two peaks in the PL spectra, suggesting the formation of an additional acceptor‐related recombination pathway leading to the observed shorter carrier lifetime.